MODERASI KINERJA KEUANGAN PADA PENGARUH STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT DI INDEKS SRI KEHATI TAHUN 2013-2017 - Bayu Saputro Utomo (Universitas Negeri Surabaya, 2021)
This Research aims to examine the effect of ownership structure on sustainability reports disclosure of companies listed on SRI KEHATI index in Indonesian Stock Exchange, with financial performance as a moderating variable. The ownership structure as an independent variable is proxied by managerial ownership, institutional ownership, and foreign ownership, while the dependent variable is sustainability report disclosure, and the moderating variable of research is financial performance. The object of this research is companies that have been registered of the SRI KEHATI index from 2013-2017. Based on the results of testing using the WarpPLS software, this research shows that from the three construct equations the maximum results are obtained in the first construct equation, that managerial ownership structure that shows influence to sustainability disclosure with financial performance which is able to moderate it.